2012
DOI: 10.1128/aac.00038-12
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Safety and Efficacy of Daptomycin versus Standard-of-Care Therapy for Management of Patients with Osteomyelitis Associated with Prosthetic Devices Undergoing Two-Stage Revision Arthroplasty

Abstract: The prevalence of Staphylococcus aureus causing prosthetic joint infection (PJI) supports investigation of higher doses of daptomycin in the management of PJI. This was a prospective, randomized controlled trial studying safety and efficacy of daptomycin (6 and 8 mg/kg of body weight) compared with standard-of-care therapy for PJI. This open-label study randomized 75 patients undergoing 2-stage revision arthroplasty to daptomycin at 6 or 8 mg/kg or a comparator (vancomycin, teicoplanin, or semisynthetic penici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 25 publications
3
72
0
Order By: Relevance
“…Emergence of daptomycin resistance remains a rare event in staphylococci and is limited to individual case reports [9,10]. While recent clinical data assessed the efficacy and safety of high-dose daptomycin in Gram-positive osteoarticular infections [2][3][4][5][6], no specific study evaluated the combined regimen of high-dose daptomycin (8 mg/kg/day) and rifampicin (600 mg/day) in this context. In view of the quite variable (from 300 to 1,200 mg/day) regimens of rifampicin that have been described in the literature, official recommendations for a standard rifampicin regimen in the context of osteoarticular infections would be most appropriate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emergence of daptomycin resistance remains a rare event in staphylococci and is limited to individual case reports [9,10]. While recent clinical data assessed the efficacy and safety of high-dose daptomycin in Gram-positive osteoarticular infections [2][3][4][5][6], no specific study evaluated the combined regimen of high-dose daptomycin (8 mg/kg/day) and rifampicin (600 mg/day) in this context. In view of the quite variable (from 300 to 1,200 mg/day) regimens of rifampicin that have been described in the literature, official recommendations for a standard rifampicin regimen in the context of osteoarticular infections would be most appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate a growing interest in the design of novel therapeutic protocols for deep-seated multi-resistant Gram-positive infections, as alternatives to the standard glycopeptide therapy [2][3][4][5][6][7][8]. Daptomycin has attractive properties for treating osteoarticular infections, because of its rapid bactericidal activity against susceptible as well as multi-resistant, Gram-positive isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success was defined as resolution or improvement of baseline clinical and radiologic findings and negative cultures at the ''testof-cure visit'' (conducted at hospital discharge or within 2 weeks after reimplantation if still hospitalized). Byren et al [7] concluded that daptomycin ''was considered safe and appeared to be effective in managing staphylococcal PJI using a two-stage revision arthroplasty technique.'' From the perspective of the current study definition, the cited randomized controlled trial evaluated the results using an extremely short time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the definition of infection eradication might include amputation; our multidimensional approach limits problems of this nature. In a recent Level-1 study involving patients undergoing two-stage revision for PJI, the use of intravenous daptomycin was compared with standard-of-care therapy [7]. The primary end point was creatine phosphokinase (used to measure the safety of the intervention).…”
Section: Discussionmentioning
confidence: 99%